2015
DOI: 10.1590/s0100-204x2015001000011
|View full text |Cite
|
Sign up to set email alerts
|

Frações ótimas da adubação com fósforo no pré-plantio e na fertirrigação por gotejamento de tomateiro

Abstract: Resumo -O objetivo deste trabalho foi estabelecer frações ótimas da dosagem total de fósforo, a serem aplicadas no pré-plantio e na fertirrigação do tomateiro de crescimento determinado, bem como determinar o efeito das diferentes formas de aplicação do nutriente sobre sua distribuição espacial no solo. Os tratamentos consistiram de cinco esquemas de aplicação do fertilizante: 100, 75, 50, 25 e 0% da dose total de P, dividida entre o pré-plantio (superfosfato triplo incorporado ao solo) e a fertirrigação (ácid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 11 publications
0
7
0
5
Order By: Relevance
“…Fertilization directly affects tomato yield, as found for the productivity of the tomato variety Azad T-6 under the application of different levels of fertilizer (Kumar et al, 2013). Additionally, levels of fertilizer lower than the doses applied in this study provided maximum productivity in tomato (Zhang et al, 2010;Marouelli et al, 2015), which in turn, is attributed to the characteristics of the soil where these studies were carried out since the application of high levels of fertilizing might result in the leaching of nutrients. The contrast in the results obtained with the cultivars Karina TY and Azad T-6 may be attributed to differences in their genetic background, besides environmental differences between the areas where these cultivars have been studied such as soil, temperature, and precipitation (Zhang et al, 2010).…”
Section: Discussionmentioning
confidence: 83%
“…Fertilization directly affects tomato yield, as found for the productivity of the tomato variety Azad T-6 under the application of different levels of fertilizer (Kumar et al, 2013). Additionally, levels of fertilizer lower than the doses applied in this study provided maximum productivity in tomato (Zhang et al, 2010;Marouelli et al, 2015), which in turn, is attributed to the characteristics of the soil where these studies were carried out since the application of high levels of fertilizing might result in the leaching of nutrients. The contrast in the results obtained with the cultivars Karina TY and Azad T-6 may be attributed to differences in their genetic background, besides environmental differences between the areas where these cultivars have been studied such as soil, temperature, and precipitation (Zhang et al, 2010).…”
Section: Discussionmentioning
confidence: 83%
“…Possibly, the higher average value estimated from SS obtained only with dose of 50 kg ha -1 of P 2 O 5 in fertigation may be explained due to the balance on in soil P availability in adequate levels throughout crop cycle (Marouelli et al 2015), making greater absorption possible for plants. It was observed that pulp pH increased in fruits cultivated with P dose up to 76 kg ha -1 of P 2 O 5 both in foundation and foundation together with fertigation ( Figure 2C).…”
Section: Resultsmentioning
confidence: 96%
“…Pre-planting fertilization, besides the fact that may increase the initial in-solution level of P for root development, compromises the availability of nutrient throughout crop cycle. On the other side, combining pre-planting fertilization with fertigation may balance the in-solution P availability to adequate levels during plant cycle (Marouelli et al, 2015). Even though P has a large influence over growth and yield, there is not much information if it brings a great effect on fruit quality.…”
Section: Introductionmentioning
confidence: 99%
“…Também, por se tratar de um solo arenoso, pode ter ocorrido perdas por percolação, fatores que em conjunto contribuíram para uma menor absorção do nutriente pela planta. Marouelli et al (2015) afirmam que a aplicação de P via fertirrigação possibilita que o mesmo se movimente no solo por fluxo de massa, o que aumenta a movimentação do nutriente no solo, sendo esse deslocamento preferencialmente no sentido vertical, uma vez que, esse é o sentido predominante de movimento da água de irrigação. Tal observação pode explicar um dos fatores responsáveis pelos menores valores de produtividade e de espessura da casca para aqueles tratamentos com menor frequência de fertirrigação.…”
Section: Resultsunclassified